Peran Masjid sebagai Sentra Dakwah Moderasi - Kurniawan, Andri (Jurnal Komunikasi Islam, 2020)
Mosques as mosaics of Islamic civilization have a variety of functions. Islamic civilization, from the classical period (650-1250 AD) to the current modern period, has a central institutional movement through the mosque. This study discusses the role of mosques as public spheres and centres for proselytisation of moderation. By using library research, this study illustrated that the mosque as an institutional centre of the implementation of worship both mahdloh and mu 'amalah. In addition, the mosque also functions as a public space in solving various problems of society as well as as a centre for preaching based on moderate Islamic values. The results of this study will enrich the treasure of the development of the role of the mosque in the current era to become a centre for socio-religious activities based on moderate Muslims.